Critical humanism and the politics of difference - Noonan, Jeff (McGill-Queen's University Press, 2003)
"Critical Humanism and the Politics of Difference takes look at sex, gender, ethnicity, and race as different ways of expressing an underlying human nature or essence. While the most influential theorists of oppression have argued that belief in some shared human essence is ultimately responsible for the injustices suffered by women, First Nations peoples, blacks, gays and lesbians, and colonized people, and have insisted that struggles against oppression must be mounted from the unique different perspectives of individual groups, Jeff Noonan argues instead that such differences must be seen to be anchored in a conception of human beings as self-creative. Unless freedom and self-determination are accepted as universal values, the moral force of arguments against exclusion and oppression is lost."--Jacket